If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -73 = 5n + 78 Reorder the terms: -73 = 78 + 5n Solving -73 = 78 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -73 + -5n = 78 + 5n + -5n Combine like terms: 5n + -5n = 0 -73 + -5n = 78 + 0 -73 + -5n = 78 Add '73' to each side of the equation. -73 + 73 + -5n = 78 + 73 Combine like terms: -73 + 73 = 0 0 + -5n = 78 + 73 -5n = 78 + 73 Combine like terms: 78 + 73 = 151 -5n = 151 Divide each side by '-5'. n = -30.2 Simplifying n = -30.2
| (y-x+1)=1 | | sqrtx-2=x-8 | | 8x-7=-3(-12x-1)+4(-7x-3) | | 8x-7=-3(-12-1)+4(-7x-3) | | x/3-88/3x=1 | | 4x^2+3x-200=0 | | 20(0.25)+14(3)+5(0.5)= | | -7/2x+16/4x=-2/4 | | 4x^2-3x-200=0 | | 35(0.25)+15(3)+5(0.5)= | | 3(1/2+1/2y)+2y=-9 | | 35(0.25)+14a+5b=49.5 | | 4x+15=25 | | 0=-z^3(9-z)+4z(2+3z) | | 20(0.25)+15a+5b=56.25 | | 0=m(5m-2)+9(5-m) | | 12+16+30/7 | | 0=2(3r^2+4r+2)-3(-r^2+4r-5) | | 2x+3=-23 | | 0=(3p+5)(3p+5) | | 3c+4u=33 | | 0=(x^4-3x^2+2)-(-2x^4+x^2-3) | | 2*60-60= | | 2(2x-7)+2x=22 | | =60+60 | | 0=(r+3)(r+3)(r+3)(r+3) | | 4*60-2*60= | | 4x-2*(60)+2x-(60)=180 | | 0=(z-3)(z-3)(z-3) | | 5p+3=14 | | (x-6)(x-4)=-16 | | 4x-2*(-60)+2x-(-60)=180 |